Phylogeography of the Eurasian red squirrel (Sciurus vulgaris orientis) on the boreal island of Hokkaido, Japan. Issue 11 (26th March 2016) - Noda, Maiko; Oshida, Tatsuo; Abramov, Alexei V.; Baranova, Galina; Baryshinikov, Gennady; Ichikawa, Hideo; Masuda, Ryuichi
Abstract: To test postglacial population expansion in small arboreal mammals dependent on boreal and subboreal forests, we used complete mitochondrial cytochrome b gene sequences (1140 bases) to investigate the phylogeography of the Eurasian red squirrel ( Sciurus vulgaris orientis ) on the Hokkaido Island of Japan. This subspecies is common in the boreal and subboreal forests of Hokkaido. We examined 61 specimens from 27 localities in Hokkaido. Phylogenetic relationships among 29 haplotypes found in the Hokkaido populations were not associated with geographic distribution of sampling localities. There were four mitochondrial DNA phylogroups. Phylogeographic analyses support sudden expansion of S. vulgaris orientis from restricted refugium in the southern part of Hokkaido during the last glacial period. The phylogeographic structure of this subspecies directly reflects the boreal and subboreal forest dynamics occurring in Hokkaido.